Law, development and finance datasets 1990-2013 - Deakin, Simon F. (UK Data Service, 2020)
Data on laws governing shareholder and creditor protection in 30 countries for the period 1990-2013. 'Leximetric' data coding methods were used to construct the datasets. These involve the development of a coding algorithm or protocol to score legal rules according to how far they protect shareholder and creditor interests in the governance of business firms. The units of analysis are countries and the laws are coded annually. The primary data used to construct the datasets are laws in the forms of texts which were retrieved from law libraries or from internet sources. The data are presented in spreadsheets which indicate the scores for individual variables by country/year, accompanied by explanatory documents which set out the coding algorithms and provide legal sources for the scores recorded in the spreadsheets. Additional qualitative data result from interviews conducted in the case-study countries. In the case of China and Russia, these are in the form of anonymised interview transcripts based on verbatim notes taken by the interviewers during the interview and typed up afterwards (as interviewees did not want to be recorded). In the case of Brazil and India, they are in the form of audio files. The aim of the project was to analyse to what extent the quality of legal and other formal institutions affected financial development and economic growth in the BRIC countries, and whether reliance on informal institutions posed an obstacle to their future growth. For over a decade, with the encouragement of the World Bank and western governments, developing countries have adopted programmes of legal and financial reform combining privatisation of state-owned banks and enterprises with the enactment of enhanced legal protections for shareholders and creditors. According to some accounts, China’s recent experience demonstrates the value of a developing legal framework in overcoming limits to growth in an informal, trust-based economy, while Russia is actively seeking to put in place the necessary legal and regulatory structures for market-based financial development. In Brazil, the example of the Novo Mercado, a new stock market segment which has attracted a large number of high-tech IPOs, suggests that a strategy of allowing firms to opt into a shareholder-rights based regulatory regime can work in promoting flows of equity finance in an emerging market context. In India, too, there is some evidence that recent corporate governance reforms have led to greater transparency on the part of listed firms and to increased investor confidence, although critics of the reform process argue that it has not gone far enough. The picture emerging from these experiences is one in which formal and informal institutions do not necessarily operate in tension. Rather, they may complement each other in providing the foundations for sustainable economic growth and societal development.